More than a century of direct glacier mass-balance observations on Claridenfirn, Switzerland - Huss, Matthias; id_orcid:0 000-0002-2377-6923; Bauder, Andreas; id_orcid:0 000-0001-7197-7706; Linsbauer, Andreas; Gabbi, Jeannette; Kappenberger, Giovanni; Steinegger, Urs; Farinotti, Daniel; id_orcid:0 000-0003-3417-4570 (International Glaciological Society, 2021)
Glacier mass-balance observations at seasonal resolution have been performed since 1914 at two sites on Claridenfirn, Switzerland. The measurements are the longest uninterrupted records of glacier mass balance worldwide. Here, we provide a complete re-analysis of the 106-year series (1914–2020), focusing on both point and glacier-wide mass balance. The approaches to evaluate and homogenize the direct observations are described in detail. Based on conservative assumptions, average uncertainties of 0.25 m w.e. are estimated for glacier-wide mass balances at the annual scale. It is demonstrated that long-term variations in mass balance are clearly driven by melting, whereas decadal changes in accumulation are uncorrelated with mass balance and can only be relevant in short periods. Mass change of Claridenfirn is impacted by dry calving at a frontal ice cliff. Considerations of ice volume flux at a cross-profile reveal long-term variations in frontal ice loss accounting for 9% of total annual ablation on average. The effect of changes in frontal ablation mostly explains 10% of the mass-balance difference relative to the period 1960–1990, but accounts for 20% in 2010–2020. Glacier mass changes are discussed in the context of observations throughout the European Alps indicating that Claridenfirn is regionally representative. ISSN:0022-1430 ISSN:1727-5652